2015
DOI: 10.1097/qad.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus vaccination induces strong human papilloma virus specific cell-mediated immune responses in HIV-infected adolescents and young adults

Abstract: The ability of a quadrivalent human papilloma virus (HPV)-16/18/6/11 virus-like particles vaccine (Gardasil) to elicit HPV-specific cell-mediated immune responses was evaluated in antiretroviral therapy (ART)-treated HIV-infected young adults. Results showed that, after three doses of vaccine, central memory and effector memory CD4(+) and CD8(+) T lymphocytes, as well as HPV-specific interleukin (IL)2(+)/CD4(+), interferon-gamma (IFN-γ(+))/CD4(+), IFN-γ(+)/CD8(+) and tumour necrosis factor-alpha (TNF-α)(+)/CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, vaccination in the general HIV‐positive population is considered safe. Early studies reported transient increases in plasma viral load following vaccination in HIV‐positive patients; more recent studies did not confirm these results . International guidelines consistently recommend vaccination of HIV‐positive individuals using inactivated vaccines.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, vaccination in the general HIV‐positive population is considered safe. Early studies reported transient increases in plasma viral load following vaccination in HIV‐positive patients; more recent studies did not confirm these results . International guidelines consistently recommend vaccination of HIV‐positive individuals using inactivated vaccines.…”
Section: Resultsmentioning
confidence: 98%
“…Early studies reported transient increases in plasma viral load following vaccination in HIV-positive patients 26,27 ; more recent studies did not confirm these results. [28][29][30][31][32] International guidelines consistently recommend vaccination of HIV- Atopic patients 3.5 The use of hyposensitizing therapy administered by the subcutaneous or intradermal route is not contraindicated in atopic patients with haemophilia (92% consensus).…”
Section: Immunocompromised Patients With Haemophilia Should Be Vaccinmentioning
confidence: 99%
“…In studies that have most commonly employed 4vHPV, vaccination has been shown to be safe and immunogenic in HIV‐positive children ; females aged 16–23 years , 18–25 years , or 13–45 years ; males aged 22–61 years ; and males and females aged 13–27 years . Cervarix and Gardasil have also been compared in older HIV‐positive people .…”
Section: Human Papilloma Virusmentioning
confidence: 99%
“…However, two dose schedules are not recommended for those with immune compromising conditions. Recent trials indicate that HPV vaccines are safe and immunogenic in those with HIV using a three dose schedule …”
Section: Current Knowledge About the Efficacy And Safety Of Prophylacmentioning
confidence: 99%
“…Recent trials indicate that HPV vaccines are safe and immunogenic in those with HIV using a three dose schedule. [31][32][33][34][35][36][37] Clinical trials have now established the safety, efficacy and immunogenicity of a three dose schedule of a nonavalent HPV vaccine, whose composition is based on the VLP and vaccine production methods underpinning the quadrivalent vaccine with higher HPV16/18/6 VLP concentrations, more adjuvant and inclusion of the next five most commonly detected oncogenic HPV types in cervical cancers (types 31,33,45,52,58). [38][39][40] For ethical reasons, the control group in the vaccine trial was given the quadrivalent vaccine rather than a placebo.…”
Section: Current Knowledge About the Efficacy And Safety Of Prophylacmentioning
confidence: 99%